Investigating the spontaneous imbibition characteristics of continental Jurassic Ziliujing Formation shale from the northeastern Sichuan Basin and correlations to pore structure and composition. (December 2018) - Gao, Zhiye; Yang, Shuo; Jiang, Zhenxue; Zhang, Kun; Chen, Lei
Abstract: Shale gas has been successfully explored in the Sichuan Basin of China, and the marine Silurian Longmaxi Formation shale is the main gas-bearing target layer. However, economic shale gas production from continental shale layers within the Sichuan Basin is still minimal, and its potential requires further investigation. This study focuses on the pore structure and spontaneous imbibition behaviors of continental Jurassic Ziliujing Formation shale samples from northeastern Sichuan Basin. Mercury intrusion porosimetry (MIP) was used to obtain the pore-throat size distribution information and field emission-scanning electronic microscope (FE-SEM) was conducted to observe the pore structure directly. The slopes of spontaneous imbibition curves were used to indicate the oil-wet or water-wet pore connectivity, and the wettability of our shale samples was investigated qualitatively by contact angle measurements and by comparing the directional spontaneous imbibition behaviors. The effects of shale composition and pore structure on spontaneous imbibition behaviors were also investigated in this study. Our results show that organic matter (OM) pores and OM-clay interparticle pores are quite developed in Ziliujing shale samples. The protection of pore spaces by rigid minerals is also observed for these samples. The oil-wet pore connectivity is generally better than water-wet pore connectivity, which could be indicated from the higher n-decane imbibition slopes compared with water imbibition slopes. The wettability of our shale samples can be classified into "weakly more oil-wet", "more oil-wet" and "more water-wet" according to the directional spontaneous imbibition results. The well-connected oil-wet pores could also be confirmed by the fast spreading of n-decane on the sample surfaces during contact angle measurements. In summary, the continental Jurassic Ziliujing Formation shale samples used in this study contain numerous OM pores and OM-clay interparticle pores, which provide both storage spaces and adsorption sites for shale gas and contribute to the better oil-wet pore connectivity. Highlights: The wettability information was indicated from directional SI experiments. The relationship between SI behaviors and shale pore structure was discussed. Contact angle with imbibed volume could be used to evaluate the shale wettability.